Siren queen ebook - Vo, Nghi (2022)
"Lyrical, mesmerizing, and otherworldly. . . stunning proof that Nghi Vo is one of the most original writers we have today. A beautiful, brutal, monstrous Hollywood fantasy."—Taylor Jenkins Reid , New York Times bestselling author of The Seven Husbands of Evelyn Hugo Immortality is just a casting call away. World Fantasy Award Finalist Locus Award Finalist Ignyte Award Finalist An Amazon Best Book of 2022 One of NPR's Best Books of 2022 Vulture's #1 Fantasy Novel of 2022 Indie Next List Reading Group Book of 2023 Best of Year Selections at Apple Books | B&N Booksellers | LibraryReads | TIME Magazine | Oprah Daily | The Philadelphia Inquirer | Publishers Weekly | Buzzfeed | Chicago Review of Books | LitHub | Book Riot | Paste Magazine | Geek Girl Authority | Bookish | The Mary Sue | New York Public Library | Vulture | Locus Recommended Reading List | Kobo | The Quill to Live | Goodreads | L. A. Public Library | Audible | Amazon | NPR An Indie Next and LibraryReads Pick A Brooklyn Library Prize Finalist It was magic. In every world, it was a kind of magic. "No maids, no funny talking, no fainting flowers." Luli Wei is beautiful, talented, and desperate to be a star. Coming of age in pre-Code Hollywood, she knows how dangerous the movie business is and how limited the roles are for a Chinese American girl from Hungarian Hill—but she doesn't care. She'd rather play a monster than a maid. But in Luli's world, the worst monsters in Hollywood are not the ones on screen. The studios want to own everything from her face to her name to the women she loves, and they run on a system of bargains made in blood and ancient magic, powered by the endless sacrifice of unlucky starlets like her. For those who do survive to earn their fame, success comes with a steep price. Luli is willing to do whatever it takes—even if that means becoming the monster herself. Siren Queen offers up an enthralling exploration of an outsider achieving stardom on her own terms, in a fantastical Hollywood where the monsters are real and the magic of the silver screen illuminates every page. At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.